Depicting Physical And Social Fears:: Shark Graffiti On Reunion Island - Flynn, Danny; Carter, Marina (Street Art & Urban Creativity, 2018)
This short paper focuses on graffiti depicting desperate warnings over the increase in shark attacks, the threat of which has been encouraged by the idyllic feeding climate on the Indian Ocean island, and suggests a metaphorical simile of the threatening invisible and ever present malevolent force felt in the social climate of expanding inner cities through greed within capital investment.